The Utah psychotropic oversight program: collaboratively addressing antipsychotic use within youth in foster care without prior authorization - Monson, Eric T.; Shastri, Sachi; Chen, Danli; Madden, Stacy L.; Keeshin, Brooks R. (Frontiers in Psychiatry, 2023)
Objectives: Fostered youth have increased risk of exposure to trauma. Antipsychotic medications are often utilized within the foster care system, potentially to address problematic behaviors that may be associated with trauma. The Utah Psychotropic Oversight Program (UPOP) was formed to support prescribers and encourage evidence-based treatment approaches for fostered youth. However, it is unclear what impact an oversight program can have on a high turnover population and without tools such as prior authorization. This study evaluates 4 years of collected data from the UPOP program for efficacy and to identify future intervention targets.Methods: Deidentified data were collected as a routine function of the oversight program over four years (01/2019-12/2022), from individuals aged 0-18 years old (total N=8,523, 48.3% female). UPOP oversight criteria: ≤6yo + any psychotropic medication, ≥7yo + 2 or more psychotropic medications. For this analysis, youth were divided by UPOP individuals ever receiving an antipsychotic (AP) prescription (UPOP_AP; N=755, 42.3% female) or not (UPOP_NAP, N=1,006, 48.3% female) and non-UPOP fostered (N=6,762, 48.9% female). Comparisons were made across demographic and clinical variables via ANOVA, Chi-square, unpaired t-test, and logistic regression.Results: UPOP_AP more likely to be older males with behavioral diagnoses, increased polypharmacy, longer duration of fostering, and higher care level. AP prescription rates dropped from 2019-2022 from 52.8% to 39.1% for males and 43.3% to 38.2% in females with unchanged number of psychotropic prescriptions and care level across 2019-2022. UPOP_AP that discontinued AP treatment had fewer average psychotropic medications, but increased antidepressant and sleep prescriptions, as compared with individuals that remained on AP.Conclusions: Youth within the foster care system receive antipsychotics at high rates and in an uneven distribution. Prescribing practices can change in the context of supportive oversight programs without components such as prior authorization, and without increasing the need for higher levels of care. Specific emphasis on the treatment of mood, anxiety, and sleep issues may also lead to greater success in discontinuing AP treatment. Oversight may support treatment providers while reducing exposure to medications with considerable side effect burden that could cause future comorbidity.